Spesialisasi Auditor Memoderasi Kualitas Kantor Akuntan Publik, Opini Audit, Pergantian Auditor Terhadap Audit Report Lag - Sastrawan, Rahman; Perdhana, Ariefanda Iqbal; Toliang, Ermina (E-Jurnal Akuntansi, 2022)
The purpose of this study was to analyze the effect of the quality of the Public Accounting Firm (KAP), audit opinion, and auditor turnover on audit report lag with auditor specialization as a moderating variable. The research was carried out on companies in the agricultural sector of the plantation sub-sector listed on the Indonesia Stock Exchange for the 2017-2019 period. The sample data used were 13 companies with purposive sampling method, data were analyzed using the WarpPLS application with a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS), while the measurement of variables used dummy variables. The results show that the quality of KAP has a negative effect, so that it has an impact on shortening the audit report lag, while audit opinion and auditor turnover have no effect on audit report lag. Auditor specialization is able to strengthen the influence of audit opinion on audit report lag, so as to shorten audit report lag. Auditor specialization is not able to strengthen the effect of auditor turnover and KAP quality on audit report lag, so it can prolong audit report lag. Keywords : KAP Quality; Audit Opinion; Auditor Change; Auditor Specialization; Audit Report Lag.